The Japanese challenge to the American neoliberal world order : identity, meaning, and foreign policy - Lee, Yong Wook (Stanford University Press, 2008)
Lee explicitly links capitalism to Japan's particular foreign economic policy choices, offering a historically informed account of the nature and evolution of the Japanese challenge to neoliberalism. Central to his analysis are the historically and socially constructed Japanese conceptions of Japan's economic identity - conceptions that have shaped Japan's interest in challenging the American-led neoliberal world order. With historical analysis beginning in the 1870s, the book explicates several of Japan's key foreign policy choices, including the Asian Monetary Fund decision in 1997, and draws out the future policy implications of these choices.